Composites of Reactive Silica Nanoparticles and Poly(glycidyl Methacrylate) With Linear and Crosslinked Chains by in Situ Bulk Polymerization - Demir, Mustafa Muammer; Altın, Burcu; Özçelik, Serdar; Özçelik, Serdar; Demir, Mustafa Muammer (Taylor and Francis Ltd., 2010)
Composites of poly(glycidyl methacrylate) (PGMA) and L-lysine-coated silica nanoparticles with varying contents were prepared by in situ bulk polymerization using benzoyl peroxide (BPO) as free radical initiator. Silica nanoparticles covered by L-lysine molecules were synthesized using emulsion method. Dynamic light scattering measurements confirmed that the particles are highly monodisperse with the diameter of 10 nm and free of aggregates in the monomer (glycidyl methacrylate, GMA). Upon polymerization of the homogeneous particle/monomer dispersion, aggregates of individual silica nanoparticles are observed by tapping mode atomic force microscope (AFM). Amine and/or carboxylic acid sites on particle surface covalently react with the oxirane groups of the polymer backbone. The aggregation was substantially suppressed by using a difunctional comonomer divinyl benzene (DVB) in polymerization. A three-dimensional polymer network, P(GMA-DVB), forms throughout the system. This structure leads to significant progress in particle dispersion, therefore in physical properties of the resulting composite. We demonstrated that the composites prepared by crosslinked chains are thermally more stable and mechanically stiffer than those prepared by linear ones.
Keywords: Agglomeration; Crosslinked; Addition polymerization; In-situ polymerization; l-Lysine; Nanoparticles